Value-Based Segmentation of Generation Z Women Consumers of India : Replication and Validation of Model - Singh, Neetu; Nigam, Sakshi (Prabandhan: Indian Journal of Management, 2021)
This research aimed at understanding the luxury value perceptions of generation Z women consumers of India by using the luxury value perception model (LVP) given by Wiedmann et al. (2009). This study tried to validate and replicate the Wiedmann model, which categorized luxury values as financial, functional, individual, and social, using the emerging generation Z women consumers of India as a context. Data were collected from 208 women consumers across India using an online questionnaire from January – March 2021. The findings validated the usage of the LVP model to create homogeneous clusters based on the preferred luxury values of the generation Z women consumers. The overall luxury values which motivated the Indian generation Z women consumers towards luxury purchases are hedonic values (self-gift giving extravagance) followed by functional value (uniqueness) and then individual values (materialistic value). The results also validated the research done by the authors (Hennigs et al., 2012) later, finding interesting similarities between Indian, German, and US consumers. By identifying the drivers of luxury purchases for young emerging women consumers of India, the outcome of this research would enable luxury brand marketers and branders to build successful marketing strategies to be more profitable.